Spectrum slicing of a broadband light source [compact disc] - 238381 Mohamed Shabeer (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2006